A comprehensive methodology for analyzing the effectiveness of organizational management structures’ performance amidst hierarchy optimization - V. V. Makrusev; A. O. Bondarenko (Вестник университета)
The article presents the main results of modelling a rational hierarchy corresponding to the transition to a flat organizational structure in the public administration system. The organizational structure of a customs authority served as an example. The obtained results allow to evidently implement a set of measures aimed at transitioning from hierarchical to flat organizational and managerial structures. To substantiate the rational hierarchy, a comprehensive methodology for analyzing the effectiveness of organizational management structures’ performance amidst hierarchy optimization is proposed. Research methodology involved the use of queuing theory tools, economic and statistical methods as well as expert and analytical methods. Modeling proved that the flat organizational structure is more rational than the hierarchical one. This is because when the structure is flat, the speed of attending to customers’ requests increases due to the decrease in internal vertical communication links and the expansion of the horizontal ones through effective redistribution of human resources.